The Influence of Authentic Leadership on Work Engagement Mediated by Perceived Organizational Support at Dewi Sri Hotel - Giri, Putu Devita Hardianni; Indrawati, Ayu Desi (Business and Investment Review, 2025)
The dynamic work environment in the hospitality industry requires employees to maintain a high level of work engagement to ensure service quality and organizational competitiveness. One of the key factors influencing employee engagement is the leadership style applied by management. Authentic leadership is believed to foster relationships based on openness, honesty, and integrity, which in turn strengthen employees’ trust and their perception of organizational support. This perception, known as perceived organizational support (POS), reflects the extent to which employees feel that the organization values their contributions and cares about their well-being. This study aims to analyze the effect of authentic leadership and perceived organizational support on work engagement, as well as to examine the mediating role of perceived organizational support among 87 employees of Hotel Dewi Sri. Data were collected through questionnaires using a Likert scale and analyzed with Structural Equation Modeling Partial Least Square (SEM-PLS). The results show that both authentic leadership and perceived organizational support have a positive and significant influence on work engagement. Authentic leadership also has a positive and significant effect on perceived organizational support, while perceived organizational support acts as a complementary partial mediator in the relationship between authentic leadership and work engagement. These findings reinforce social exchange theory, which emphasizes that authentic leadership behavior encourages perceptions of organizational support, and through these perceptions, employees reciprocate by exhibiting higher levels of work engagement. The practical implications highlight the importance of communication transparency, value consistency, and concern for employee well-being as strategic approaches to enhance work engagement and overall organizational performance.